Leveraging Foreign Higher Education Institutional Affiliation to Support Preservation of Local Knowledge and Fight Displacement in Thailand - Collins, Lauren (Frontiers: The Interdisciplinary Journal of Study Abroad, 2022)
Study abroad host families and communities in the Global South frequently provide learning experiences to study abroad programs in search of ‘intercultural experiences’ and ‘global competency’ to students from the Global North. This paper shares findings from a multi-sited ethnographic research project exploring cultural and economic impacts on host communities in Thailand who hosted U.S. study abroad programs and students. The study found that rather than participating solely for economic gain, host families participated in the global study abroad economy to preserve local knowledge, learn about cultural others, and leverage this knowledge and affiliations in negotiations with local government over land use and the right of communities remain in place. It also found that creation of systems of distributive benefit (systems that ensured transparency and equal sharing of economic benefits received from hosting students) by local government helped to mitigate unwanted impacts from outside visitors while allowing host communities opportunities to engage with the global study abroad economy.